Toxicity and biochemical effects of four pesticides on honey bee, Apis mellifera under laboratory conditions - Z. M. Al Dhafar; M. A. Abdel Razik; M. A. Osman; M. E. Sweelam (Brazilian Journal of Biology)
Abstract The widespread use of insecticides can cause negative side effects on pollinators, resulting undesirable effects in crop productivity. So, this study was conducted to evaluate the toxicity and biochemical changes in honey bees, Apis mellifera (Hymenoptera: Apidae) enzymes, treated with four insecticides i.e. lambda-cyhalothrin, hexythiazox, fenpyroximate and thiamethoxam under laboratory conditions. The obtained results revealed that thiamethoxam was extremely toxic to A. mellifera adults (LC50=0.006 ppm) followed by lambda-cyhalothrin (LC50=0.053 ppm) and fenpyroximate (LC50=2.29 ppm) after 24 h of treatment, however, hexythiazox was relatively less toxic to bees (110.09 ppm). The sub-lethal concentration LC25 and LC50 of tested pesticides, reduced the activity of AChE, GST, MFO and esterase’s activities in honey bee adults, where, lambda-cyhalothrin and thiamethoxam induced the highest effects compared with other two pesticides and control. In contrast, the tested insecticides activated PPO enzyme at LC25 concentration, while PPO activity was reduced after treating adult bees with LC50. Lambda-cyhalothrin, thiamethoxam, fenpyroximate and hexythiazox disrupted the physiology of honey bees, thereby reducing the efficiency of this beneficial pollinator. Overall, the obtained results are valuable not only in evaluating the toxicity of common insecticides onto honey bees, but also in highlighting the validity of enzyme activities as appropriate indicators for exposure to agrochemicals.